Breeding for silicon-use efficiency, protein content and drought tolerance in bread wheat (Triticum aestivum L.): a review. (31st December 2022) - Christian, Marylyn M.; Shimelis, Hussein; Laing, Mark D.; Tsilo, Toi J.; Mathew, Isack
ABSTRACT : The production and quality of wheat are affected by abiotic constraints including water stress and soil nutrient deficiencies. It is imperative to develop drought-tolerant wheat varieties with high yield potential and enhanced grain protein content for food security. Silicon (Si) is important for plant growth and development but its role in abiotic stress tolerance has been overlooked in breeding programs. Identifying the underlying functional genes controlling drought tolerance, protein content and grain yield is essential for wheat improvement, especially under drought stress. Silicon uptake is conditioned by several Si transporter genes such as Lsi1, Lsi2 and Lsi6 and aquaporins, which facilitate transport of silicon and water between cells. The objectives of this review are to examine the role of Si in improving plant nutrition and drought tolerance, and to appraise the genetic control of Si uptake and breeding methods for improving Si uptake for drought adaptation and improved grain yield and quality. The review highlights the limited progress made in breeding for drought tolerance in wheat, especially in sub-Sahara Africa where the challenge is prevalent. Limited understanding of the genetic basis for Si uptake and physiology contribute to the limited progress in its exploitation in wheat improvement programs.